Influence of the addition of vanadium to Pt/TiO2 catalyst on the selective catalytic oxidation of NH3 to N2. Issue 19 (24th August 2019) - Kim, Geo Jong; Kwon, Dong Wook; Shin, Jung Hun; Kim, Ki Wang; Hong, Sung Chang
ABSTRACT: In this work, the effect of the addition of vanadium to the Pt/TiO2 catalyst on the selective catalytic oxidation (SCO) of NH3 to N2 was investigated. It was found that the addition of vanadium significantly enhanced catalytic activity at all tested temperatures. The Pt/V/TiO2 catalyst exhibited the highest NH3 conversion (∼100%) and NH3 to N2 conversion (∼81%) at 250°C. The physicochemical characteristics of the catalysts were investigated via Brunauer-Emmett-Teller (BET) analysis, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), NH3 temperature-programmed desorption (TPD), NH3 temperature-programmed oxidation (TPO), and in situ Fourier-transform infrared (FTIR) spectroscopy. It was found that the addition of V to the catalyst enhanced the conversion of NH3 as a result of the formation of new acid sites. The increase in the number of acid sites resulted in increased NH3 to N2 conversion via the internal selective catalytic reduction (i-SCR) mechanism. This mechanism involves the SCR of NO x, which are formed by the oxidation of NH3 . Based on experimental results and analyses of the catalysts modified by the addition of V, it was shown that there was a close relation between reaction selectivity and the surface oxygen species of the catalyst and N2 yield. Furthermore, the addition of V increased the durability of SO2 by inhibiting the formation of ammonium bisulfate (ABS). GRAPHICAL ABSTRACT: